HEMINGWAY HEROES IN “THE SUN ALSO RISES” AND “FOR WHOM THE BELL TOLLS” = NHÂN VẬT NAM CHÍNH TRONG TIỂU THUYẾT “MẶT TRỜI VẪN MỌC” VÀ “CHUÔNG NGUYỆN HỒN AI”CỦA ERNEST HEMINGWAY - Trần, Thị Huyền Anh (2021)
The thesis is generally divided into three chapters. Chapter I, namely literature review, deals with literary concepts and methods of characterization. Also, the researcher would like to include in this chapter a brief introduction to the author Hemingway and his “iceberg principle” in the two novels “For Whom the Bell Tolls” and “The Sun also Rises”. The focus of this thesis falls on chapter 2 and chapter 3 in which the author tries to analyse hero characterization of other writers and the characteristics of Hemingway heroes in these two novels in particular and the entire works of Hemingway in general. A quick view and general remark on the content and artistic value of the two novels acts as a conclusion for the whole thesis.